Simulation Framework Development for the Multidisciplinary Optimisation of Rotorcraft - Goulos, Ioannis (Cranfield University, 2012)
The effective and efficient evaluation of conceptual product designs prior to manufacturing of prototypes, is of utmost importance for any industrial ac¬tivity. The rotorcraft industry is no different. Accurate, thorough and cost-effective evaluation of conceptual rotorcraft designs requires an equivalently rigorous and simultaneously affordable methodology covering all aspects rel¬ative. The associated issues to be tackled are indeed multi-dimensional and include trim performance, rotor blade structural loads prediction, engine per¬formance, mission analysis and associated environmental impact. The aforementioned topics are now raising even more interest as rotorcraft traffic is expected to grow sharply within the next 20 years. Current rotorcraft operations imply the consumption of the equivalent of 400,000 tons of aviation fuel per year, only with regards to the European region. Maintaining current rotorcraft technologies is expected to lead to a quadruplicating of this figure. This is a direct result of the expected traffic augmentation. In recognition of this trend, a wide range of research & development activities is currently being undertaken at national and European levels. The objective is to effectively return within 20 years to the present global level of environmental impact, while sustaining the expected growth of rotorcraft services. The objective set above is indeed an ambitious one. Due to the rather short time-scales involved, its realization requires for focus to be placed predomi¬nantly on the design of operational procedures. It is however realized that, in order to manage the environmental impact of civil rotorcraft aviation within larger time-scales, options concerning the design of conceptual configurations as well as incorporated operational procedures, need to be explored. Two fundamental requirements are therefore identified and addressed within this work. The 1st lies with regards to a generic methodology capable of design¬ing optimum operational procedures in terms of fuel burn, gaseous emissions and ground noise impact. The 2nd can be designated as a design assessment approach, capable of estimating the overall fuel consumption with regards to any designated operation. The employed method has to be capable of being utilized within the task of design while simultaneously maintaining a reasonable computational overhead so as to be applicable in the context of multidisciplinary optimization. This work elaborates on the development and application of an integrated approach, targeting the comprehensive assessment of combined helicopter– engine designs, within complete, three-dimensional operations. A series of individual modeling methods has been developed, each applicable to a dif-ferent aspect of helicopter flight dynamics and performance. These comprise rotor blade modal analysis, aeroelasticity, flight dynamics trim solution, en-gine performance and three-dimensional flight path definition. The individual mathematical models are elaborately integrated within a numerical procedure solving for the total mission fuel consumption. Extensive validation with ex-isting experimental and numerical data has been waged during each step of the development process. The aspect of multidisciplinary design of optimum rotorcraft operations in terms of fuel burn and environmental impact is also tackled within the con-text of this work. An existing integrated tool capable of estimating the per-formance and emitted noise of any defined rotorcraft configuration within any designated mission has been incorporated. A comprehensive and cost-effective optimization strategy has been structured. The methodology has been applied to two generic – baseline missions representative of current rotorcraft opera¬tions. Missions optimally designed in a multidisciplinary manner for fuel burn, gaseous emissions and ground noise impact have been obtained. The contribution to knowledge arising from the successful completion of this work, broadly comprises the development of methodologies applicable to the following aspects of civil rotorcraft aviation: (i) Comprehensive analysis of the overall flight dynamics and performance of any designated helicopter–engine integrated system, within realistically defined three-dimensional missions; (ii) Multidisciplinary design of optimum rotorcraft operations in terms of fuel consumption, gaseous and ground noise impact; Further to the above, con-tribution has been made through the analytical development of modeling ap-proaches with application to: (i) Rotor blade modal analysis; (ii) Treatment of rotor blade flexibility; (iii) Rotor–fuselage aerodynamic interaction. The developed analytical methods have been utilized within this work to facilitate the achievement of the set objectives. The potential to comprehensively eval-uate integrated helicopter–engine systems within complete three-dimensional operations, based on the solution of the aeroelastic behavior of the main rotor is demonstrated. The ability to design optimum operations in a multidisci¬plinary fashion using only a single design criterion has been exhibited.